Complication rates of acellular dermal matrix in immediate breast reconstruction with radiation: A single-institution retrospective comparison study. Issue 12 (December 2020) - Stein, Michael J.; Chung, Amy; Arnaout, Angel; Ghaedi, Bahareh; Ghumman, Ammara; Zhang, Tinghua; Zhang, Jing
Abstract: Background: The use of acellular dermal matrix (ADM) in immediate breast reconstruction (IBR) continues to rise despite ongoing concerns with respect to increased complication rates. While the indications for radiation continue to broaden, it is essential to critically evaluate ADM's performance in its context. The purpose of this study was to review complication rates between patients reconstructed with and without ADM, who underwent IBR and radiation. Methods: A retrospective review was performed for patients undergoing IBR and radiation from 2010 to 2019. Postoperative outcomes were compared between patients with and without ADM. Results: Over a 9-year period, 130 patients underwent IBR and radiation (42% preoperatively and 59% postoperatively). For patients with preoperative radiation (36 ADM and 18 non-ADM), the average follow-up was 312 and 296 days, respectively. In this group, there was no difference in minor complications (25% ADM, 22% non-ADM, and p  = 1.00) or major complications (31% ADM, 22% Non-ADM, and p  = 0.52). For patients with postoperative radiation (53 ADM and 23 non-ADM), the average follow-up was 544 and 748 days, respectively. There was no difference in minor complications (21% ADM, 26% non-ADM, and p  = 0.11) or major complications (21% ADM, 26% non-ADM, and p  = 0.61). Multivariable logistic regression analyses showed no difference between ADM and non-ADM groups (OR 0.83, 95% CI 0.22–3.08, and p  = 0.78). Conclusion: Despite increasing literature supporting the use of ADM in breast reconstruction, postoperative outcomes following radiation remain poorly understood. In the present study, we report no difference in overall complication rates between breasts reconstructed with and without ADM in an irradiated field. Nevertheless, the complication rate remains high, and future studies will be required to determine whether ADM-associated complications in an irradiated field outweigh the purported benefits.